2021
DOI: 10.3390/jcm10102118
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis Associated Episcleritis and Scleritis: An Update on Treatment Perspectives

Abstract: Episcleritis and scleritis are the most common ocular inflammatory manifestation of rheumatoid arthritis. Rheumatoid arthritis (RA) accounts for 8% to 15% of the cases of scleritis, and 2% of patients with RA will develop scleritis. These patients are more likely to present with diffuse or necrotizing forms of scleritis and have an increased risk of ocular complications and refractory scleral inflammation. In this review we provide an overview of diagnosis and management of rheumatoid arthritis-associated epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Episcleritis is the second most common ocular manifestation of RA, affecting approximately 1–5% of RA patients [13,32]. The episclera is a thin connective tissue layer that lies between Tenon's capsule and the scleral stroma.…”
Section: Episcleritismentioning
confidence: 99%
“…Episcleritis is the second most common ocular manifestation of RA, affecting approximately 1–5% of RA patients [13,32]. The episclera is a thin connective tissue layer that lies between Tenon's capsule and the scleral stroma.…”
Section: Episcleritismentioning
confidence: 99%
“…As the ocular surface plays such a critical role in defense microorganisms and other threats, the eye is susceptible to inflammation or immunologic disorders and shows different ophthalmological manifestations that may be early symptoms in some rheumatic disease cases, ahead of systemic vasculitis (40). This study found ocular microvascular changes which may precede the diagnosis of the underlying RA (41-43).…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Approximately 5% of patients with RA may develop episcleritis, and 2% may develop scleritis. [ 2 ] Patients with recurrent or recalcitrant scleritis tend to have persistent circulating antibodies like RF, ANA, and ANCA. [ 3 ] It is mandatory to rule out infectious causes before treatment.…”
Section: Discussionmentioning
confidence: 99%